Design of a Challenging Prosthetic Fitting Process and Rehabilitation Training Program to Achieve Functionality in a Complex Quadruple Amputee - Madroñero-Mariscal, Raquel; Palmero-Valdez, Natalia; González-Parra, Emilio; Izquierdo, Raúl Ramos; Marcelino, Ricardo; Llaneras, María Pérez-Cuesta; Nasarre, Barbara; Rueda, Almudena Fernández-Bravo; López-Dolado, Elisa; Melton, Danielle H (Archives of Clinical and Medical Case Reports, 2023)
Purpose: Despite the increase in the technological prosthetics development, there is no consensus to decide the best fit for amputees. The aim of the present case report is creating a comprehensive guide to choose the best prosthetic option for a quadruple amputee, focusing on the prosthetic fitting process and rehabilitation. Methods: A novel TASKA terminal device for the myoelectric prosthesis for transradial right upper limb amputation was the key to do the training for activities of daily life and recover independence. The rehabilitation program was vital to achieve the objective. Results: The prosthetic chosen options and the rehabilitation plan resulted in a useful and aesthetically acceptable option. After training, there was an improvement on PLUS-M, DASH Scale, Barthel Index and EQ-D-VAS Scale, all related to the patient wearing prostheses. Conclusions: In order to regain this patient’s basic functions, it was important to start the training with the right upper limb. The TASKA terminal device, recently made available in Spain, has helped her with the donning and doffing of her lower limb prostheses. No prosthetic for left partial amputated hand was needed. As for the lower extremities, microprocessor knees with stance control for safety have demonstrated to be the most appropriate.